USM EMPOWERMENT EFFORTS HAVE YIELDED GLOBAL-MINDED STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, April 2016 The move by Universiti Sains Malaysia (USM) in empowering its students has yielded positive results. The students of today have the tenacity in exploring their own potentials as global players in speaking their minds on issues which transcend boundaries.